THE SYNTHESIS OF COPPER(II)-CONTAINING 1,2,4-TRIAZOLE COMPLEXES: UDC 541.49+546.791.6-381+547.792.4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Methods of the synthesis of the copper(II) containing 3-(2-pyridinyl)-1H-1,2,4-triazole complexes are reported. Systematic studies were devoted to the investigating an importance of triethylamine towards the сomplexation. The various coordination modes that have been observed in complexes were discussed. We noticed the correlations of coordination complexes structure and the metal-ligand correlation. Two mononuclear complexes and one dinuclear complex of a 2:2 composition were obtained. The deprotonation of the ligand in the complex namely [Cu(L)2](H2O)2 was eased by adding triethylamine. The octahedral complex [Cu(HL)2(NO3)](NO3) was synthesized without triethylamine.  In excess of ligands, mononuclear coordination compounds formed mostly. By adding the equal to ligand amount of triethylamine we obtained complex in a lower tetragonal symmetry. Deprotonated triazole is the high field ligand, therefore, due to the Jahn–Teller effect, square coordination is more desirable. In all coordination compounds formation of the 5-membered chelate cycle realizes through a pyridine-triazole binding site.The structures of three complexes have been determined by single crystal X-ray diffraction.
Keywords: 1,2,4-triazole, copper(II) complexes, X-raycrystallography